Clinical Evaluation of Intravitreal Injection of Ganciclovir in Refractory Corneal Endotheliitis. (17th February 2020) - Yu, Ting; Peng, Rong-Mei; Xiao, Ge-Ge; Feng, Li-Na; Hong, Jing
ABSTRACT: Purpose : To evaluate the efficacy and safety of intravitreal ganciclovir (GCV) injection in refractory endotheliitis. Methods : Retrospectively recruited 25 eyes with endotheliitis, proved by clinical manifestations, positive PCR for viral DNA and responded poor to topical and systemic antiviral medications. All patients received additional continued intravitreal GCV injections. Results : Cytomegalovirus (CMV), varicella zoster virus (VZV), and herpes simplex virus (HSV) DNA were detected in 64.0%, 28.0%, and 8.0% of the eyes, respectively. Within 2 weeks after the last injection, 16/25 eyes recovered corneal clarity; active keratic precipitates (KPs) were eliminated in 21/25 eyes; intraocular pressure (IOP) was controlled in 12/15 eyes with elevated IOP on study entry. Best-corrected visual acuity increased at the last follow-up ( p = 0.016). Clinical recurrence occurred in three patients. No complications were detected. Conclusions : CMV endotheliitis was the main type of refractory endotheliitis. Despite its invasive nature, intravitreal GCV injection appears to be an effective method for refractory endotheliitis.